2010
DOI: 10.1021/jp1000607
|View full text |Cite
|
Sign up to set email alerts
|

Study of 2-H-Heptafluoropropane and Its Thermal Decomposition Using UV Photoelectron Spectroscopy and ab Initio Molecular Orbital Calculations

Abstract: The thermal decomposition of 2-H-heptafluoropropane, CF(3)CHFCF(3), at low pressure, heavily diluted in argon, has been studied over the temperature range 600-2000 degrees C using photoelectron spectroscopy. Comparison of the results obtained has been made with results of recent electronic structure calculations of possible decomposition pathways and results of a shock tube study. The most favored reaction thermodynamically, to produce CF(3)CF=CF(2) + HF, is found to be the main decomposition reaction at lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…One would be tempted to conclude from these results that reaction (1) followed by the faster reaction (3) dominates C 2 F 5 H decomposition. Likewise, one might conclude that C 3 F 7 H decomposition is dominated by reaction (5) followed by the faster dissociation of C 3 F 6 to 3 CF 2 . However, our detailed studies of the concentration dependence of the kinetics of CF 2 formation showed that this conclusion is premature and a more complicated mechanism of radical reactions has to be considered.…”
Section: Experimental Techniques and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One would be tempted to conclude from these results that reaction (1) followed by the faster reaction (3) dominates C 2 F 5 H decomposition. Likewise, one might conclude that C 3 F 7 H decomposition is dominated by reaction (5) followed by the faster dissociation of C 3 F 6 to 3 CF 2 . However, our detailed studies of the concentration dependence of the kinetics of CF 2 formation showed that this conclusion is premature and a more complicated mechanism of radical reactions has to be considered.…”
Section: Experimental Techniques and Resultsmentioning
confidence: 99%
“…The product yields measured in ref. 5, therefore, do not correspond to those relevant for high pressure practical applications.…”
Section: Decomposition Of Cf 3 Cfhcfmentioning
confidence: 93%
See 3 more Smart Citations